Samsodhan Therapy in the Management of Udavartani W.S.R. to Primary Dysmenorrhea; A Case Report (Bheshaja: Journal of Central Ayurveda Campus, 2025)
Dysmenorrhoea is one of the most common complaints in women at every age and especially in young reproductive life. In the ancient literatures, it can be closely related as Udavartani Yonivyapad, whereas in the modern medical science it is known as dysmenorrhoea. Modern treatment approaches usually incorporate usage of NSAID or surgery, but the main target for treatment of primary dysmenorrhoea is symptomatic relief. Apatient of primary dysmenorrhea presented and was managed with Samsodhan (Yog Basti) Ayurveda protocol, which showed a significant improvement in assessment parameters. Asthapana Basti was given with Dashmool Trivrit and Anuvasana Basti was given with Dashmool Tail. The treatment plan targeted to normalise the normal pace and direction of Apana Vayu, to enable normal flow of menstrual blood and relieve Vataja symptoms like pain, Udavartan, etc. The case study thus highlights the effectiveness of the Samsodhan Vidhi in addressing gynecological conditions at their root.